POTENCIALIDADES DOS EXPERIMENTOS NA APRENDIZAGEM SIGNIFICATIVA DOS CONCEITOS FÍSICOS DE HIDROSTÁTICA - Bulegon, Ana Marli (2006)
The purpose of this work was to investigate the contributions of the experimental activities while a classroom resource in a meaningful process of teaching-learning of Hydrostatics in High Schools. To reach this objective we have made experimental activities, with own schedules, inserted in Didactics Modules, developed according to the Three Pedagogical Moments, proposed by Delizoicov and Angotti (1991). The accomplishment of these activities occurred in the Physics laboratory of Manoel Ribas Public School in Santa Maria/RS, in a second group of students. These activities used recycle and/or material that can easily get in the students neighborhood and they where utilized to complement the conceptual approach in the expositive teaching about the topics studied. In this work we have used the learning theory of Ausubel, which offers us a theoretical reference that makes possible to improve the Physics teaching with few or no conditions or resources like in a great number of public schools. According to this theory, meaningful learning is a process that must begin trough the previous knowledge of the students, obtained through their personal experiences and buildings in the environment they are inserted and their interaction with new acquirements using teaching-learning activities that make the relationship among theses procedures easier. The acquired results of these activities showed that there was an evolution in the construction of meanings of Physics concepts involved in this subject. When they have handled recycle material the students have noticed that science is not a finished knowledge that belongs just a limited group of people but it can be studied and understood by all of us as we take part of it. The investigation has shown up that the work with classroom experimental activities has allowed the development of students attitudes and proceedings that lead them to approximate their school reality and their everyday life and also can help them to solve not only school doubts but also everyday life problems.